Hypoxic blackwater event severely impacts Murray crayfish (Euastacus armatus) populations in the Murray River, Australia. (11th February 2014) - McCarthy, Bernard; Zukowski, Sylvia; Whiterod, Nick; Vilizzi, Lorenzo; Beesley, Leah; King, Alison
Abstract Prolonged flooding in 2010/11 ended a decade of drought and produced a large‐scale hypoxic blackwater event across the southern Murray‐Darling Basin, Australia. The hypoxic conditions caused fish kills and Murray crayfish Euastacus armatus to emerge from the water onto the river banks to avoid the poor water quality. This study examined the medium‐term impact of this blackwater event on Murray crayfish populations in the Murray River, where approximately 1800 km of the main channel were affected by hypoxia. Murray crayfish populations were surveyed in July 2012, along a 1100‐km section of the Murray River at 10 sites affected by hypoxic blackwater and six sites that were not affected, and data were compared with surveys of the same sites undertaken in July 2010, four months before the hypoxic blackwater event (before‐after‐control‐impact experimental design). Murray crayfish abundance in 2012 (post‐blackwater) was significantly lower at blackwater affected sites (81% reduction from 2010), but not at non‐affected sites. The hypoxic blackwater impacted Murray crayfish of both sexes and all size‐classes in a similar manner. The results demonstrate that prolonged periods of hypoxia can markedly impact populations of the long‐lived and slow‐growing Murray crayfish despite the species ability to emerge from hypoxic water. The findings highlight important challenges for the management of both the recreational fishery for this species and riverine flows in relation to hypoxic blackwater events.